Extracellular vesicles secreted from bone metastatic renal cell carcinoma promote angiogenesis and endothelial gap formation in bone marrow in a time-dependent manner in a preclinical mouse model - Takeda, Masashi; Sakamoto, Hiromasa; Shibasaki, Noboru; Fukui, Tomohiro; Magaribuchi, Toshihiro; Sumiyoshi, Takayuki; Utsunomiya, Noriaki; Sawada, Atsuro; Goto, Takayuki; Kobayashi, Takashi; Ueda, Koji; Yamasaki, Toshinari; et al. (Frontiers in Oncology, 2023)
Bone is a major metastatic site of renal cell carcinoma (RCC). Recently, it is well recognized that bone metastatic tumor cells remodel bone marrow vasculature. However, the precise mechanism underlying cell-cell communication between bone metastatic RCC and the cells in bone marrow remains unknown. Extracellular vesicles (EVs) reportedly play crucial roles in intercellular communication between metastatic tumor cells and bone marrow. Therefore, we conducted the current study to clarify the histological alteration in vascular endothelium in bone marrow induced by EVs secreted from bone metastatic RCC cells as well as association between angiogenesis in bone marrow and bone metastasis formation. For this purpose, we established a bone metastatic RCC cell line (786-O BM) by in vivo selection and observed phenotypic changes in tissues when EVs were intravenously injected into immunodeficient mice. Treatment of mice with EVs from 786-O BM promoted angiogenesis in the bone marrow in a time-dependent manner and increased the gaps of capillary endothelium. The 786-O BM EVs also promoted tube formation in vitro. Proteomic analysis of EVs identified aminopeptidase N (APN) as a candidate protein that enhances angiogenesis. APN knockdown in 786-O BM resulted in reduced angiogenesis in vitro and in vivo. Consequently, when parental 786-O cells were intracardially injected 12 weeks after treatment with 786-O BM EVs, more bone metastasis developed compared to those treated with EVs from parental 786-O cells. Finally, we examined whether tissue-exudative EVs (Te-EVs) from bone metastatic RCC patients (BM-EVs) contained higher APN compared to Te-EVs from patients with locally advanced RCC (LA-EV). BM-EVs contained higher APN and promoted tube formation in vitro compared to LA-EVs. Collectively, our data show that EVs from bone metastatic RCC promote angiogenesis and gap formation in capillary endothelium in bone marrow in a time-dependent manner.